2013
DOI: 10.2146/ajhp120769
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining the process for initial review of pharmacy residency applications: An analytic approach

Abstract: By analyzing the relative importance of specific residency applicant characteristics and focusing on those deemed most useful in determining which candidates are invited for interviews, a large teaching institution streamlined preliminary application screening while maintaining an equitable candidate selection process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 8 publications
3
59
0
Order By: Relevance
“…This contrasts with our model where letters of recommendation, community service, letters of intent, and leadership experience were shown to be significantly associated with likelihood of interview. 6 Explanations for these discrepancies could be a A J P E A c c e p t e d D r a f t difference in criteria for scoring, different candidate populations applying to the programs, and the difference in scale between our screening tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with our model where letters of recommendation, community service, letters of intent, and leadership experience were shown to be significantly associated with likelihood of interview. 6 Explanations for these discrepancies could be a A J P E A c c e p t e d D r a f t difference in criteria for scoring, different candidate populations applying to the programs, and the difference in scale between our screening tools.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recently, Ensor and colleagues made assessments of the screening tool used at their institution. 6 Our own study was conducted with the purpose of adding to the sparse amount of published literature by performing similar analyses in order to provide additional insights into the screening process, and to provide a point of comparison to Ensor and colleagues's results.…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate analysis of factors that were significantly associated with invitation to interview at one residency program (Johns Hopkins Hospital) included professional association involvement, presentations, practices experiences, publications, pharmacy work experience, pharmacy school GPA, and skills and certifications. 7 Although extracurricular activities did not have a direct association with matching, students should not be discouraged from participating in these activities as they may learn valuable skills necessary for successful completion of a residency program.…”
Section: Discussionmentioning
confidence: 99%
“…6 At the Johns Hopkins Hospital, Ensor et al sought to streamline the approach to screening pharmacy residency applications. 7 Factors found to be most strongly predictive of offering an interview were professional association involvement, presentations, practice experiences, publications, work experience, GPA, and certifications. Theoretically, all of these preparation strategies and recommendations can increase students' chances of obtaining interviews and matching.…”
Section: Introductionmentioning
confidence: 99%
“…In the years preparing for postgraduate opportunities, including residency and fellowships, students are expected to seek opportunities for research experience and community service. 3 Cardell and colleagues surveyed lecture recording viewing habits of all first-year and second-year students at Harvard Medical School. The authors concluded 29.4% of medical students relied only on lecture recordings.…”
mentioning
confidence: 99%